Low-voltage polymer transistors on hydrophobic dielectrics and surfaces. (2nd March 2023) - Kraft, Ulrike; Nikolka, Mark; Wang, Ging‐Ji Nathan; Kim, Yeongin; Pfattner, Raphael; Alsufyani, Maryam; McCulloch, Iain; Murmann, Boris; Bao, Zhenan
Abstract: A set of unique features, including large-area solution processing on flexible and stretchable substrates, make polymer semiconductors a promising material choice for a range of state-of-the-art applications in electronics, optoelectronics and sensing. Yet, an inherent weakness of polymer semiconductors remains their low dielectric constants, increasing their susceptibility toward unscreened dipoles. These dipoles are particularly prevalent at polymer-dielectric interfaces with high- k dielectrics, which are essential for the operation of devices such as low-voltage field-effect transistors. This shortcoming can be addressed by using self-assembled monolayers (SAMs) to passivate surfaces that impact charge transport. However, SAM-treatment also increases the hydrophobicity of surfaces and therefore poses a challenge for subsequent solution processing steps and complex packaging of devices. Here, we report low-voltage polymer transistors processed by spin coating of the polymer semiconductors on highly hydrophobic SAM-treated aluminum and hafnium oxide dielectrics (contact angles >100) through fine-tuning of the interfacial tension at the polymer-dielectric interface. This approach enables the processing and detailed characterization of near-amorphous (indacenodithiophene- co benzothiadiazole) as well as semicrystalline ( poly(2, 5-bis(2-octyldodecyl)-3, 6-di(thiophen-2-yl)diketopyrrolo[3, 4-c]pyrrole-1, 4-dione-alt-thieno[3, 2-b]thiophen )) polymer semiconductors. We demonstrate polymer transistors that exhibit high on-currents and field-independent, charge carrier mobilities of 0.8 cm 2 V −1 s −1 at low operating voltages (<3 V).